2015
DOI: 10.1007/s10637-015-0257-z
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of saracatinib (AZD0530) in patients with previously treated metastatic colorectal cancer

Abstract: Saracatinib is a novel oral Src kinase inhibitor that was well tolerated but failed to meet its primary endpoint of improvement in 4 month progression-free survival as a single agent in previously treated metastatic colorectal cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 37 publications
3
22
0
Order By: Relevance
“…might inhibit other kinases in addition to Src, such as Lck, c-YES, Lyn, Fyn, Fgr and Blk. It has been shown that AZD0530 effectively reduces Src kinase activity in non-small cell lung cancer and colorectal cancer (Chua et al, 2015;Reddy et al, 2015). Moreover, our screening results in Figure 3A showed that only Src and Tnk2, but not other tyrosine kinases (Lck, c-YES, Lyn, Fyn, Fgr and Blk), functioned as the possible upstream kinases of pY433-MST1.…”
Section: Discussionmentioning
confidence: 77%
“…might inhibit other kinases in addition to Src, such as Lck, c-YES, Lyn, Fyn, Fgr and Blk. It has been shown that AZD0530 effectively reduces Src kinase activity in non-small cell lung cancer and colorectal cancer (Chua et al, 2015;Reddy et al, 2015). Moreover, our screening results in Figure 3A showed that only Src and Tnk2, but not other tyrosine kinases (Lck, c-YES, Lyn, Fyn, Fgr and Blk), functioned as the possible upstream kinases of pY433-MST1.…”
Section: Discussionmentioning
confidence: 77%
“…Its activity results in inhibition of cell proliferation (causing G 0 /G 1 arrest), as well as inhibition of cell adhesion, migration, invasion and tumour metastasis [44,53, [139][140][141][142][143]. Despite the encouraging clinical results for the use of dasatinib as a standalone therapy in CML, clinical findings with dasatinib or alternative Src/ABLkinase inhibitors (saracatinib, bosutinib) [145,146] in PDAC were predominately negative, partially due to poor drug tolerance, but also due to the highly aggressive and adaptable nature of this disease to singleagent targeted therapies and rapid onset of resistance [53,138,[147][148][149][150][151][152][153][154][155][156]. Despite the encouraging clinical results for the use of dasatinib as a standalone therapy in CML, clinical findings with dasatinib or alternative Src/ABLkinase inhibitors (saracatinib, bosutinib) [145,146] in PDAC were predominately negative, partially due to poor drug tolerance, but also due to the highly aggressive and adaptable nature of this disease to singleagent targeted therapies and rapid onset of resistance [53,138,[147][148][149][150][151][152][153][154][155][156].…”
Section: Targeting Src Kinase In Pancreatic Cancermentioning
confidence: 99%
“…These results were particularly promising in models of advanced PDAC, presenting dasatinib as an encouraging antimetastatic agent for this disease [29,56,144]. Despite the encouraging clinical results for the use of dasatinib as a standalone therapy in CML, clinical findings with dasatinib or alternative Src/ABLkinase inhibitors (saracatinib, bosutinib) [145,146] in PDAC were predominately negative, partially due to poor drug tolerance, but also due to the highly aggressive and adaptable nature of this disease to singleagent targeted therapies and rapid onset of resistance [53,138,[147][148][149][150][151][152][153][154][155][156]. Moreover, the presumption that these biologic agents would significantly improve survival in nonstratified cohorts, particularly in PDAC, is inconsistent with prior preclinical data, which suggests that therapeutic response may correlate with biological markers.…”
Section: Targeting Src Kinase In Pancreatic Cancermentioning
confidence: 99%
“…However, at 2 μ mol/L saracatinib, which effectively inhibited SFK and ABCB1 activities in VR cells, the drug concentration was remarkably higher than the serum concentration in patients from a previous study who took once‐daily 175‐mg doses of saracatinib . This finding may be a causative factor in the negative clinical trial results for NSCLC and other malignancies .…”
Section: Discussionmentioning
confidence: 80%